The characteristics of intestinal microbiota in patients with type 2 diabetes and the correlation with the percentage of T-helper cells - Yang, Fan; Li, Jinyan; Wei, Longqin; Qin, Shenghua; Shi, Qingfeng; Lu, Siyan; Chu, Shuyuan (Frontiers in Microbiology, 2024)
Background: Type 2 diabetes (T2D) is related with intestinal microflora changes and immune inflammation. We aim to investigate the pattern of intestinal flora-systematic Th cells linkage in T2D patients. Methods: Subjects with T2D diagnosed by physicians and healthy controls were enrolled into study. Th1, Th2 and Th17 cells from peripheral blood were assessed by flow cytometry. Feces were collected. The V3-V4 variable region of 16S rRNA was sequenced and analyzed in bioinformatics. Principal Coordinates Analysis (PCoA) and Non-metric Multidimensional Scaling (NMDS) analysis were performed to assess the beta diversity. The linear discriminant analysis (LDA) effect size method (LEfSe) was applied to identify a microbial taxa specific to T2D. The Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) was conducted to identify the metabolic pathways. The network analysis was performed by constructing co-occurrence network. Results: The percentage of Th1 and Th17 in peripheral blood were higher in T2D patients than controls. Among top 30 genus of intestinal microbiota, the level of Lachnospiraceae_NK4A136_group, Ruminococcaceae_UCG002 and Eubacterium_hallii_group was respectively lower in T2D patients than controls. From LEfSe analysis, Lachnospiraceae and Ruminococcaceae families were significantly different between T2D subjects and controls. Moreover, Th1/Th2 ratio was positively correlated with the abundance of Lachnoclostridium and Ruminococcus_torques_group genus. In network analysis, Th1/Th2 ratio, Ruminococcaceae_UCG-002 and Lachnospiraceae_NK4A136_group were important nodes. Conclusions: This study provides a preliminary picture of the crosstalk between the intestinal microbiome and systematic Th cells in T2D patients. Those findings suggest that the network relationship among intestinal microbiota, metabolites, and CD4+T lymphocyte immunity were unbalanced in T2D patients, which may promote the development of T2D. That presents a therapeutic opportunity to modulate gut immune reaction and then chronic inflammation by manipulating microbiome-specific Th cell response.